Utilization of services at community-based intimate partner violence agencies: associations with sociodemographic and victimization factors - PettyJohn, Morgan E. (Journal of family violence, 2025)
Purpose: To assess what sociodemographic and victimization factors are associated with past year service use at community-based intimate partner violence (IPV) agencies. Methods: Using a quantitative, web-based survey, we assessed sociodemographic characteristics, victimization experiences, and past year service use at community-based IPV agencies among a diverse, urban-based sample (n = 432) of participants who reported past year IPV victimization. Results: Over a quarter of participants (29%) reported accessing community-based IPV services in the past year. We used logistic regression to examine associations between past year service use and 15 sociodemographic and victimization factors. In the final model, 8 factors were significantly associated with service use. Men (OR = 0.18, p = .002), Hispanic victims (OR = .34, p = .013; compared to non-Hispanic white), and those with higher income (OR = .70, p = .01) were less likely to use community-based IPV services, while people with children (OR = 3.0, p = .002) accessed at higher rates. People experiencing sexual IPV were the most likely to seek services (OR = 4.16, p < .001), followed by coercive control (OR = 3.17, p = .001), and recent gun threats (OR = 2.46, p = .048). Surprisingly, people reporting physical IPV were significantly less likely (OR = .34, p = .009) to access these services. Conclusions: While additional research is warranted, these findings can be used to inform expanded outreach efforts, risk assessment, and culturally specific practice models to increase service use at community-based IPV agencies among certain survivor groups.